Utilization of Eucalyptus hybrid (Mysore Gum) Bark for Production of Oxalic Acid - Prabhu, V. V.; Theagabajan, K. S. (Indian Forester, 1977)
Large scale plantations of Eucalyptus hybrid (Mysore gum; mainly E. tereticormis) are being undertaken to meet the increasing demand of pulpwood industry. The bark of the tree has no use at present, and in view of its availability in plenty it can be used as a raw material for producing oxalic acid. Laboratory trials yielded 40-45% of oxalic acid by oxidation process. Its use in place of tannin rich bark of Terminalis species is suggested.